Advanced Cooling Technologies and Applications - Sohel Murshed, S. M. (IntechOpen, 2019)
Since conventional cooling techniques are increasing falling short of meeting the ever-growing cooling demands of high heat generating devices, thermal systems, and processes, advanced and innovative cooling technologies are of immense importance to deal with such high thermal management. Hence, this book covers a number of key topics related to advanced cooling approaches, their performance, and applications, including: Evaporative air cooling; Spray impingement cooling; Heat pump-based cooling; Modular cooling for photovoltaic plant; Nucleate pool boiling of refrigerants; Transient flashing spray cooling and application; Compressor cooling systems for industry. The book is aimed at a wide variety of people from graduate students and researchers to manufacturers who are involved or interested in the areas of thermal management systems, cooling technologies, and their applications.